The Apostolic Fathers - Clement I, Pope.; Ignatius Saint, Bishop of Antioch, d. ca. 110.; Polycarp Saint, Bishop of Smyrna.; Lightfoot, Joseph Barber (Macmillan, 1885)
pt. I. S. Clement of Rome. A revised text with introductions, notes, dissertations, and translations. [2d ed.] 1890. 2 v.--pt. II. S. Ignatius. S. Polycarp. Revised texts, with introductions, dissertations, and translations. 1885. 3 v.